Physicochemical properties of β-cyclodextrin solutions and precipitates prepared from injectable vehicles - Sai Myo Thurein; Nutdanai Lertsuphotvanit; Thawatchai Phaechamud (Elsevier, 2018)
β-Cyclodextrin (β-CyD) is cyclic oligosaccharide of a glucopyranose, containing a relatively hydrophobic central cavity and hydrophilic outer surface. However, the usefulness of β-CyD is limited owing to its low aqueous solubility whereas we found that its apparent high solubility was evident in some injectable solvents including 2-pyrrolidone (PYR), N-methyl pyrrolidone (NMP) and dimethyl sulfoxide (DMSO). Therefore, in the present study, the physicochemical properties of the 30-60% w/w β-CyD in PYR, NMP and DMSO were investigated such as viscosity, water resistant, matrix formation rate and syringeability. The higher the concentration of β-CyD resulted in the increased viscosity and the higher force and energy of syringeability. β-CyD in PYR gave the highest viscosity which contributed to the lowest syringeability while β-CyD in DMSO exhibited the highest syringeability. The β-CyD in DMSO and NMP exhibited the higher rate of matrix formation. β-CyD in PYR showed the highest water resistant for phase separation while β-CyD in NMP gave the faster de-mixing rate compared to that from PYR. The difference in physicochemical properties of β-CyD dried ppts studied by scanning electron microscope (SEM), differential scanning calorimetry (DSC), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA) revealed that there was partial complexation of β-CyD with respective solvents. Both solution and precipitate characteristic properties will be useful for using β-CyD in further investigation as matrix material dissolved in the injectable vehicles as the in situ forming gel for periodontitis treatment. Keywords: β-CyD solution, Precipitates, Dimethyl sulfoxide, N-methyl pyrrolidone, 2-pyrrolidone, Matrix formation